Regulation and function of Myb-binding protein 1A (MYBBP1A) in cellular senescence and pathogenesis of head and neck cancer - George, Babitha; Horn, Dominik; Bayo, Pilar; Plath, Karim; Flechtenmacher, Christa; Grabe, Niels; Plinkert, Peter K.; Heß, Jochen (Cancer letters, 2014)
Myb-binding protein 1A (MYBBP1A) is a nucleolar protein implicated in stress response and carcinogenesis; however, its functional contribution to senescence remains elusive. In this study we show decreased MYBBP1A protein levels in tumor cells after treatment with etoposide, a potent inducer of DNA damage. Although silencing of MYBBP1A expression was not sufficient to induce senescence, it significantly increased the relative abundance of senescent cells after DNA damage. We found an inverse regulation of MYBBP1A and AKT phosphorylation (pAKT(Ser473)), which was characteristic for the pre-senescent state after etoposide administration in vitro. Tissue microarrays with tumor specimens from primary oropharyngeal squamous cell carcinoma (OPSCC) patients (n = 61) by immunohistochemistry revealed a significant correlation between MYBBP1AlowpAKT(Ser473)high staining pattern and shorter progression-free (p = 0.007) or overall survival (p < 0.001). Multivariate analysis showed that MYBBP1AlowpAKT(Ser473)high staining pattern is an independent prognosticator for OPSCC. Taken together, our study points to a critical role of MYBBP1A in the regulation of senescence under genotoxic stress and that a MYBBP1AlowAKT(Ser473)high staining pattern serves not only as a marker for the pre-senescent stage but also as an indicator of OPSCC patients at high risk for treatment failure.
Gesehen am 16.08.2017